2022
DOI: 10.1093/conphys/coac073
|View full text |Cite
|
Sign up to set email alerts
|

Neotropical stingless bees display a strong response in cold tolerance with changes in elevation

Abstract: Tropical pollinators are expected to experience substantial effects due to climate change, but aspects of their thermal biology remain largely unknown. We investigated the thermal tolerance of stingless honey-making bees, the most ecologically, economically and culturally important group of tropical pollinators. We assessed changes in the lower (CTMin) and upper (CTMax) critical thermal limits of 17 species (12 genera) at two elevations (200 and 1500 m) in the Colombian Andes. In addition, we examined the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…This does not follow the trend within colonies of tropical ants for largerbodied workers to have higher heat tolerance and lower cold tolerance (Cerdáand Retana, 1997;Baudier et al, 2018;Roeder et al, 2021). Our results more closely follow the lack of relationship between intraspecific size variation and thermal tolerance in bumblebees (Maebe et al, 2021) and honeybees (Sańchez-Echeverrıá et al, 2019;Barreiro et al, 2024), and are in-line with cross-species comparisons of tropical stingless bees that found no relationship between body size and either upper or lower thermal tolerance (Gonzalez et al, 2022c). However, we report that foragers did have a larger thermal tolerance breadth than hovering guards or standing guards.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…This does not follow the trend within colonies of tropical ants for largerbodied workers to have higher heat tolerance and lower cold tolerance (Cerdáand Retana, 1997;Baudier et al, 2018;Roeder et al, 2021). Our results more closely follow the lack of relationship between intraspecific size variation and thermal tolerance in bumblebees (Maebe et al, 2021) and honeybees (Sańchez-Echeverrıá et al, 2019;Barreiro et al, 2024), and are in-line with cross-species comparisons of tropical stingless bees that found no relationship between body size and either upper or lower thermal tolerance (Gonzalez et al, 2022c). However, we report that foragers did have a larger thermal tolerance breadth than hovering guards or standing guards.…”
Section: Discussionsupporting
confidence: 45%
“…Other studies in temperate climates have found that increasing body size is correlated with decreasing cold tolerance across and within several species (Peters et al, 2016), and a significant effect of increasing body size on increasing heat tolerance and decreasing cold tolerance across three Bombus species (Oyen et al, 2016). In a few examples of tropical bee species, one study reports larger body sizes across four Bombus species were correlated to lowered CT min (when looking within species, this trend was only maintained in one species) while there was no effect on CT max across species (Gonzalez et al, 2022a), and another study reports no strong relationship between size and thermal tolerance across stingless bee species (Gonzalez et al, 2022c). It is not yet clear whether there is a reliable size-tolerance relationship trend in bee species, and it is especially unclear whether any trends exist between polymorphic castes within genetically similar colonies of a single species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation